Crossing the sound barrier: telefilms and acoustic flow in early Spanish television. (3rd July 2019) - Vernon, Kathleen M.
ABSTRACT: This essay argues for the relevance of television to the interdisciplinary field of sound studies. For scholars R. Murray Schafer and Jonathan Sterne, the study of sound is deeply contextual and linked to the experience of social, environmental and technological change. While most television theory and history is based on US and UK models, I seek to understand the factors that shaped the development of the television industry in Spain, how the population perceived and responded to the changes to social habits and norms brought, or accompanied, by television, and the ways television altered the soundscape of mid-twentieth-century Spain in contexts both public and private. From Raymond Williams (2004, Television: Technology and Cultural Form . 3rd ed. New York: Routledge) I borrow the notion of televisual "flow" – used to describe the actual experience of television viewing structured as a continuous sequence of diverse fragments, less concerned with semantic content as with other sensory and affective inputs and responses – adapted here to foreground the sounds of television and audience perception of those sounds. I home in on a set of television programs and an especially charged acoustic space, that of so-called telefilms, imported American series dubbed into Spanish in Latin America and transmitted on the single Spanish channel during prime evening viewing hours.